Phase Change Materials and Their Applications - Mhadhbi, Mohsen (IntechOpen, 2018)
Today, the application of phase change materials (PCMs) has developed in different industries, including the solar cooling and solar power plants, photovoltaic electricity systems, the space industry, waste heat recovery systems, preservation of food and pharmaceutical products, and domestic hot water. PCMs use the principle of latent heat thermal storage to absorb energy in large quantities when there is a surplus and release it when there is a deficit. This promising technology has already been successfully implemented in many construction projects. The aim of this book is to assist the scientists and to provide the reader with a comprehensive overview of the properties that characterize the phase change materials from theoretical and experimental perspectives with a focus on their technological applications. The present status and future perspectives of phase change material are discussed.